A method for preparing a composite separator for sodium-ion batteries

By coating a sodium-ion battery separator with ceramic fiber powder prepared by electrospinning, the compatibility problem of existing lithium-ion battery separators in sodium-ion batteries is solved, improving the thermal stability, electrolyte wettability and mechanical strength of the separator, improving the migration efficiency of sodium ions, and extending the cycle life of the battery.

CN122267430APending Publication Date: 2026-06-23KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610293855.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-11
Publication Date
2026-06-23

AI Technical Summary

Technical Problem

Existing lithium-ion battery separators are difficult to adapt to sodium-ion batteries in terms of pore structure, ion transport efficiency and thermal stability, and have problems such as poor heat resistance, insufficient electrolyte wettability and difficulty in suppressing dendrite growth.

Method used

Ceramic fiber powder was prepared by electrospinning and mixed with a binder to form a coating slurry. This slurry was then coated onto the surface of a polyolefin membrane to form a porous coating, creating continuous ion transport channels and enhancing the membrane's thermal stability and mechanical strength.

Benefits of technology

It significantly improves the thermal stability, electrolyte wettability, and mechanical strength of sodium-ion batteries, enhances the migration efficiency of sodium ions, and extends the cycle life and electrochemical performance of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122267430A_ABST
    Figure CN122267430A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of sodium ion batteries, in particular to a preparation method of a composite diaphragm for a sodium ion battery, which comprises the following steps: preparing nanoscale ceramic fiber powder by electrostatic spinning combined with high-temperature sintering; mixing the ceramic fiber powder and a binder in a solvent to form coating slurry; and casting the slurry on at least one surface of a polyolefin porous base film to form a porous coating layer containing ceramic fibers after drying, thereby obtaining a composite diaphragm. The ceramic fibers have a nanoscale diameter and a high aspect ratio, and can form a continuous three-dimensional network structure in the coating layer. The composite diaphragm prepared by the application can improve the thermal stability, electrolyte wettability and mechanical strength of the diaphragm, and effectively improve the transmission efficiency of sodium ions. When the diaphragm is applied to a sodium ion battery, the battery shows excellent cycle stability and rate performance, the capacity retention rate is significantly improved, and the diaphragm has a good practical prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology, and more specifically to a method for preparing a composite separator for sodium-ion batteries. Background Technology

[0002] With the ongoing global push for carbon peaking and carbon neutrality, energy storage systems have become a key technology supporting large-scale grid integration of renewable energy, enabling flexible power system dispatch, and ensuring the safe operation of the power grid. Among these, electrochemical energy storage, with its advantages of rapid response, bidirectional regulation, and strong environmental adaptability, has become an important development direction for current energy storage technology. Lithium-ion batteries are widely used in electrochemical energy storage systems due to their high energy density and excellent electrochemical performance; however, limited by lithium resource shortages and cost issues, they struggle to meet the economic demands of future large-scale energy storage. Sodium-ion batteries, with their abundant sodium resources and low cost, have become a potential alternative technology to lithium-ion batteries. However, sodium-ion batteries suffer from problems such as the large radius of sodium ions and slow ion migration kinetics, leading to higher requirements for membrane materials. Existing lithium-ion battery membranes are not fully compatible with sodium-ion batteries in terms of pore structure, ion transport efficiency, and thermal stability, necessitating the development of novel membrane materials and modification strategies specifically for sodium-ion batteries.

[0003] As a crucial component of sodium-ion batteries, the separator needs to possess high porosity, good thermal stability, and mechanical strength. While commonly used polyolefin separators have mature manufacturing processes, they suffer from drawbacks such as poor heat resistance, insufficient electrolyte wettability, and difficulty in effectively suppressing dendrite growth. Surface coating of polyolefin separators with ceramic materials is an important approach to improving their overall performance and has been widely applied in the lithium-ion battery field.

[0004] Compared to traditional ceramic particles, ceramic fibers possess a higher aspect ratio, enabling the construction of continuous ion transport channels within the separator, significantly improving ion migration efficiency, and effectively enhancing the separator's mechanical properties and thermal stability. In particular, α-Al₂O₃ nanofibers, due to their excellent high-temperature resistance, chemical stability, and electrolyte wettability, are considered highly promising modified materials. Currently, research on ceramic fiber-modified polyolefin separators remains relatively scarce, indicating significant room for technological development. Therefore, developing methods for preparing ceramic fiber-modified polyolefin separators has important research value and application prospects for improving the thermal safety, ion transport performance, and overall electrochemical performance of sodium-ion batteries. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing a composite separator for sodium-ion batteries. The method involves preparing ceramic fibers by electrospinning and coating them onto the surface of a polyolefin separator. The resulting separator exhibits excellent thermal stability and electrochemical performance.

[0006] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution: A method for preparing a composite separator for sodium-ion batteries includes the following steps: Provides polyolefin porous base membranes; Ceramic fiber powder and binder are mixed in a solvent to form a coating slurry, wherein the ceramic fiber powder has a fibrous morphology and the diameter of the ceramic fiber is on the nanoscale. The coating slurry is applied to at least one surface of the polyolefin porous base membrane and dried to form a porous coating containing the ceramic fiber powder on the surface of the polyolefin porous base membrane, thereby obtaining the composite membrane.

[0007] Furthermore, the ceramic fiber powder is prepared by a method including the following steps: mixing a ceramic precursor sol with a polymer spinning aid and then electrospinning to obtain precursor fibers, and then subjecting the precursor fibers to sintering and crushing treatment.

[0008] Furthermore, the ceramic precursor sol is a sol containing at least one of aluminum, silicon, or zirconium; the polymeric spinning aid is at least one of polyvinyl alcohol, polyvinyl butyral, or polyvinylpyrrolidone.

[0009] Furthermore, the voltage of the electrospinning is 8-20 kV, and the rotation speed is 100-1000 r / min; the temperature of the sintering treatment is 800-1500℃.

[0010] Furthermore, in the coating slurry, the mass ratio of the ceramic fiber powder to the binder is 2:1 to 20:1, and the mass ratio of the ceramic fiber powder to the solvent is 1:1 to 1:8.

[0011] Furthermore, the adhesive is a polymer adhesive, which includes oil-soluble adhesives and / or water-soluble adhesives; wherein the oil-soluble adhesive includes polyvinylidene fluoride (PVDF), and the water-soluble adhesive includes at least one of carboxymethyl cellulose (CMC) or polyethylene oxide (PEO); the solvent is a polar solvent that is compatible with the adhesive.

[0012] Furthermore, the method of applying the coating slurry to the surface of the base film is casting coating, and the drying temperature is 40-60°C.

[0013] Furthermore, the application step includes forming the porous coating on both opposite surfaces of the polyolefin porous base film, and the thickness of each porous coating after drying is independently 5-20 μm.

[0014] On the other hand, the present invention proposes a composite diaphragm prepared by the above-described preparation method.

[0015] On the other hand, the present invention proposes a sodium-ion battery comprising the above-mentioned composite separator, positive electrode, sodium negative electrode and electrolyte.

[0016] This invention utilizes one or more ceramic fibers as additives to prepare a ceramic fiber-modified polyolefin separator. The introduction of ceramic fibers significantly improves the thermal stability and electrolyte wettability of the separator. Simultaneously, it constructs continuous sodium ion transport channels within the separator, improving sodium ion migration behavior in the battery and effectively enhancing the mechanical strength of the separator. This helps suppress sodium dendrite penetration, thereby greatly improving the cycle stability and electrochemical performance of the sodium-ion battery. Sodium-ion battery performance testing (test temperature 30℃, current density 5C) shows that the initial discharge specific capacity of the sodium-ion battery using a commercial separator is 102.15 mAh g⁻¹. -1 After 1000 cycles, the specific capacity decreased to 35.75 mAh g. -1 The capacity retention rate was 35%; the initial discharge specific capacity of the sodium-ion battery prepared using a separator modified with nano-ceramic particles was 79.01 mAh g. -1 After 1000 cycles, the specific capacity is 71.64 mAh g. -1 The capacity retention rate was 90.67%; while the initial discharge specific capacity of the sodium-ion battery using a ceramic fiber modified polyolefin separator was 100.79 mAh g. -1 After 1000 cycles under the same conditions, its specific capacity can be maintained at 95.44 mAh g. -1 The capacity retention rate was 94.7%.

[0017] The beneficial effects of this invention are: This invention significantly improves the thermal stability of polyolefin membranes by introducing ceramic fibers. The ceramic fibers are prepared through electrospinning combined with high-temperature sintering, forming a stable α-crystalline structure at 1200℃, with a melting point much higher than that of the polyolefin base membrane. After being mixed with a binder and coated onto the surface of a polypropylene or polyethylene membrane, the resulting porous coating acts as a skeletal support in high-temperature environments. When the temperature rises to near the melting temperature of the polyolefin base membrane, the base membrane material softens and shrinks, while the dispersed ceramic fibers in the coating, maintaining structural integrity, effectively suppress the overall thermal shrinkage of the membrane. Figure 2 As shown, the modified separator prepared using the method of this invention can maintain its original size and morphology after high-temperature treatment, while the unmodified commercial separator shows significant shrinkage. This can prevent short circuits between the positive and negative electrodes due to separator shrinkage under overheating conditions, thereby improving the safety and reliability of sodium-ion batteries.

[0018] This invention utilizes the geometric morphology and surface chemical properties of ceramic fibers to achieve synergistic optimization of electrolyte wettability and ion transport capabilities in a membrane. The ceramic fibers possess nanoscale diameters and high aspect ratios, overlapping to form a continuous three-dimensional network structure within the coating. Unlike the point-contact stacking of traditional granular ceramic materials, the continuous porous channels in the fiber network provide a more direct migration path for sodium ions, shortening the ion transport distance within the membrane and reducing ion migration kinetic resistance. Simultaneously, the α-Al₂O₃ ceramic fiber surface is rich in polar functional groups, exhibiting good affinity for carbonate electrolytes, promoting rapid electrolyte spreading on the membrane surface and its penetration into the membrane interior. Figure 3 As shown, the modified separator of this invention exhibits a faster wetting rate and a larger wetting area within the same time frame. The improvements in the aforementioned structure and surface properties directly contribute to the electrochemical performance of the battery, such as... Figure 4 , Figure 5 As shown in Table 1, the battery assembled using the modified separator of this invention retains a specific capacity of 103.1 mAh / g after 1000 cycles at 5C, with a capacity retention of 94.7%, significantly better than the unmodified separator and the ceramic particle modified separator. The improved electrolyte wettability reduces the contact resistance at the electrode / separator interface, while the continuous fiber network channels ensure efficient migration of sodium ions during repeated charge and discharge processes. The combined effect of these two factors reduces the polarization and slows down capacity decay during long-cycle operation.

[0019] This invention enhances the mechanical strength of the separator by distributing ceramic fibers in a network within the coating, thereby improving the battery's ability to suppress sodium dendrite penetration. The α-Al₂O₃ ceramic fibers, prepared through electrospinning and high-temperature sintering, possess high intrinsic hardness and elastic modulus. After being coated onto the surface of a polyolefin-based membrane with a binder, the fibers form a continuous mechanical reinforcing phase through physical entanglement and interfacial bonding with the binder. This reinforcing phase effectively disperses localized stress when the separator is subjected to dendrite penetration forces, preventing coating cracking or base membrane penetration caused by stress concentration. The high aspect ratio of the ceramic fibers allows them to withstand tensile and shear loads in two and three dimensions. Compared to granular ceramic materials, which only provide point-like reinforcement, the reinforcing network constructed from fibrous materials exhibits superior mechanical properties. Figure 1 As shown, the coating prepared in the embodiments of the present invention has a uniform fiber distribution and interlocking structure, providing a microstructural basis for improving mechanical strength. Combined with the fact that no sudden capacity decay or short-circuit failure due to dendrite penetration was observed in Examples 3 to 5 of Table 1 during long-cycle testing, it indicates that the modified separator of the present invention has a significant advantage in suppressing sodium dendrite penetration, and is of substantial significance for improving the cycle life and reliability of sodium-ion batteries.

[0020] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Attached Figure Description

[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 Microscopic morphology diagrams of the commercial diaphragm in Comparative Example 1 and the diaphragms in Examples 1 to 5 of the present invention.

[0023] Figure 2 This is a comparison chart showing the thermal stability of the commercial diaphragm in Comparative Example 1 and the diaphragms in Examples 3 to 5 of the present invention.

[0024] Figure 3 This is a comparison chart showing the electrolyte wettability of the commercial diaphragm in Comparative Example 1 and the diaphragms in Examples 3 to 5 of the present invention.

[0025] Figure 4 This is a comparison chart showing the rate cycle performance of sodium-ion batteries made with the commercial separator from Comparative Example 1, Comparative Example 2, and the separator from Example 5.

[0026] Figure 5 This is a comparison chart showing the high-rate, long-cycle performance of sodium-ion batteries made with the commercial separator of Comparative Example 1, Comparative Example 2, and the separator of Example 5.

[0027] Figure 6 This is a schematic diagram of the preparation process of the present invention. Detailed Implementation

[0028] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1 The method for preparing a composite separator for sodium-ion batteries as described in this embodiment includes the following steps: (1) Weigh 1 mol aluminum nitrate and 0.25 mol aluminum isopropoxide and add them to 70 mL of deionized water. Stir at room temperature (25 °C) until transparent, and then reflux at 80 °C for 10 h to obtain aluminum sol. (2) Weigh a certain amount of polyvinylpyrrolidone (PVP) and dissolve it in anhydrous ethanol to prepare a 12wt% spinning aid solution; (3) Mix the above aluminum sol with PVP solution in equal volume, stir evenly and then inject into the electrospinning device. Perform electrospinning under the conditions of voltage 11kV, drum speed 280r / min and humidity 40%RH to collect nanofiber precursors. (4) The obtained fiber precursor was placed in a forced-air drying oven and dried at 60°C for 6 hours, then sintered at 1200°C for 2 hours, and then ball-milled at 1000 r / min for 2 hours to obtain nano-sized α-Al2O3 ceramic fiber powder. (5) Weigh nanofiber Al2O3:PVDF=6:1 (wt%) and add it to NMP solvent (the ratio is powder:solvent=1:3wt%). Stir at 60℃ for 12 hours to obtain ceramic fiber slurry coated with diaphragm. (6) The obtained slurry was cast onto one side of the polypropylene diaphragm with a thickness of 10 μm and dried at 40°C in a forced-air drying oven for 12 h. Then the slurry was flipped over and cast onto the other side with a thickness of 10 μm. It was dried again to obtain a double-sided coated ceramic fiber modified diaphragm. (7) The modified separator was assembled with a sodium metal sheet and a positive electrode sheet (Na3V2(PO4)3@C@CNTs) (NVP@C@CNTs were prepared by sol-gel method and annealing. Vanadium pentoxide, anhydrous oxalic acid, glucose, sodium oxalate and ammonium dihydrogen phosphate were dissolved in deionized water in proportion and stirred in a water bath at 80°C to obtain a blue solution. Carbon nanotubes were ultrasonically dispersed in ethylene glycol and then added dropwise to the above solution. The mixture was evaporated to dryness at 100°C, vacuum dried and then annealed at 750°C in an argon atmosphere to obtain the product) into a coin cell sodium-ion battery. NaPF6 / EC:DMC electrolyte was injected and constant current charge-discharge test was performed at 30°C using the Xinwei Battery Test System. The voltage range was set to 2.5-4V to test the cycle stability and rate performance.

[0030] Example 2 The method for preparing a composite separator for sodium-ion batteries as described in this embodiment includes the following steps: (1) Weigh 1 mol aluminum nitrate and 0.25 mol aluminum isopropoxide and add them to 70 mL of deionized water. Stir at room temperature (25 °C) until transparent, and then reflux at 80 °C for 10 h to obtain aluminum sol. (2) Weigh a certain amount of polyvinylpyrrolidone (PVP) and dissolve it in anhydrous ethanol to prepare a 12wt% spinning aid solution; (3) Mix the above aluminum sol with PVP solution in equal volume, stir evenly and then inject into the electrospinning device. Perform electrospinning under the conditions of voltage 11kV, drum speed 280r / min and humidity 40%RH to collect nanofiber precursors. (4) The obtained fiber precursor was placed in a forced-air drying oven and dried at 60°C for 6 hours, then sintered at 1200°C for 2 hours, and then ball-milled at 1000 r / min for 2 hours to obtain nano-sized α-Al2O3 ceramic fiber powder. (5) Weigh out nanofiber Al2O3:PVDF=8:1 (wt%) and add it to NMP solvent (the ratio is powder:solvent=1:3wt%). Stir at 60℃ for 12 hours to obtain ceramic fiber slurry coated with diaphragm. (6) The obtained slurry was cast onto one side of the polypropylene diaphragm with a thickness of 10 μm and dried at 40°C in a forced-air drying oven for 12 h. Then the slurry was flipped over and cast onto the other side with a thickness of 10 μm. It was dried again to obtain a double-sided coated ceramic fiber modified diaphragm. (7) The modified separator was assembled with a sodium metal sheet and a positive electrode (Na3V2(PO4)3@C@CNT) into a coin cell sodium-ion battery. NaPF6 / EC:DMC electrolyte was injected, and constant current charge-discharge test was performed using the Xinwei Battery Test System at 30°C. The voltage range was set to 2.5-4V, and the cycle stability and rate performance were tested.

[0031] Example 3 The method for preparing a composite separator for sodium-ion batteries as described in this embodiment includes the following steps: (1) Weigh 1 mol aluminum nitrate and 0.25 mol aluminum isopropoxide and add them to 70 mL of deionized water. Stir at room temperature (25 °C) until transparent, and then reflux at 80 °C for 10 h to obtain aluminum sol. (2) Weigh a certain amount of polyvinylpyrrolidone (PVP) and dissolve it in anhydrous ethanol to prepare a 12wt% spinning aid solution; (3) Mix the above aluminum sol with PVP solution in equal volume, stir evenly and then inject into the electrospinning device. Perform electrospinning under the conditions of voltage 11kV, drum speed 280r / min and humidity 40%RH to collect nanofiber precursors. (4) The obtained fiber precursor was placed in a forced-air drying oven and dried at 60°C for 6 hours, then sintered at 1200°C for 2 hours, and then ball-milled at 1000 r / min for 2 hours to obtain nano-sized α-Al2O3 ceramic fiber powder. (5) Weigh the nanofiber Al2O3:PVDF=10:1 (wt%) and add PVDF to NMP solvent (the ratio is powder:solvent=1:3wt%), stir at 60℃ for 12h, and stir at 700r / min to obtain ceramic fiber slurry coated with diaphragm. (6) The obtained slurry was cast onto one side of the polypropylene diaphragm with a thickness of 10 μm and dried at 40°C in a forced-air drying oven for 12 h. Then the slurry was flipped over and cast onto the other side with a thickness of 10 μm. It was dried again to obtain a double-sided coated ceramic fiber modified diaphragm. (7) The modified separator was assembled with a sodium metal sheet and a positive electrode (Na3V2(PO4)3@C@CNT) into a coin cell sodium-ion battery. NaPF6 / EC:DMC electrolyte was injected, and constant current charge-discharge test was performed using the Xinwei Battery Test System at 30°C. The voltage range was set to 2.5-4V, and the cycle stability and rate performance were tested.

[0032] Example 4 The method for preparing a composite separator for sodium-ion batteries as described in this embodiment includes the following steps: (1) Weigh 1 mol aluminum nitrate and 0.25 mol aluminum isopropoxide and add them to 70 mL of deionized water. Stir at room temperature (25 °C) until transparent, and then reflux at 80 °C for 10 h to obtain aluminum sol. (2) Weigh a certain amount of polyvinylpyrrolidone (PVP) and dissolve it in anhydrous ethanol to prepare a 12wt% spinning aid solution; (3) Mix the above aluminum sol with PVP solution in equal volume, stir evenly and then inject into the electrospinning device. Perform electrospinning under the conditions of voltage 11kV, drum speed 280r / min and humidity 40%RH to collect nanofiber precursors. (4) The obtained fiber precursor was placed in a forced-air drying oven and dried at 60°C for 6 hours, then sintered at 1200°C for 2 hours, and then ball-milled at 1000 r / min for 2 hours to obtain nano-sized α-Al2O3 ceramic fiber powder. (5) Weigh the nanofiber Al2O3:PVDF=12:1 (wt%) and add PVDF to NMP solvent (the ratio is powder:solvent=1:3wt%), stir at 60℃ for 12 hours to obtain ceramic fiber slurry coated with diaphragm. (6) The obtained slurry was cast onto one side of the polypropylene diaphragm with a thickness of 10 μm and dried at 40°C in a forced-air drying oven for 12 h. Then the slurry was flipped over and cast onto the other side with a thickness of 10 μm. It was dried again to obtain a double-sided coated ceramic fiber modified diaphragm. (7) The modified separator was assembled with a sodium metal sheet and a positive electrode (Na3V2(PO4)3@C@CNT) into a coin cell sodium-ion battery. NaPF6 / EC:DMC electrolyte was injected, and constant current charge-discharge test was performed using the Xinwei Battery Test System at 30°C. The voltage range was set to 2.5-4V, and the cycle stability and rate performance were tested.

[0033] Example 5 The method for preparing a composite separator for sodium-ion batteries as described in this embodiment includes the following steps: (1) Weigh 1 mol aluminum nitrate and 0.25 mol aluminum isopropoxide and add them to 70 mL of deionized water. Stir at room temperature (25 °C) until transparent, and then reflux at 80 °C for 10 h to obtain aluminum sol. (2) Weigh a certain amount of polyvinylpyrrolidone (PVP) and dissolve it in anhydrous ethanol to prepare a 12wt% spinning aid solution; (3) Mix the above aluminum sol with PVP solution in equal volume, stir evenly and then inject into the electrospinning device. Perform electrospinning under the conditions of voltage 11kV, drum speed 280r / min and humidity 40%RH to collect nanofiber precursors. (4) The obtained fiber precursor was placed in a forced-air drying oven and dried at 60°C for 6 hours, then sintered at 1200°C for 2 hours, and then ball-milled at 1000 r / min for 2 hours to obtain nano-sized α-Al2O3 ceramic fiber powder. (5) Weigh the nanofiber Al2O3:PVDF=14:1 (wt%) and add PVDF to NMP solvent (the ratio is powder:solvent=1:3wt%), stir at 60℃ for 12h to obtain ceramic fiber slurry coated with diaphragm. (6) The obtained slurry was cast onto one side of the polypropylene diaphragm with a thickness of 10 μm and dried at 40°C in a forced-air drying oven for 12 h. Then the slurry was flipped over and cast onto the other side with a thickness of 10 μm. It was dried again to obtain a double-sided coated ceramic fiber modified diaphragm. (7) The modified separator was assembled with a sodium metal sheet and a positive electrode (Na3V2(PO4)3@C@CNT) into a coin cell sodium-ion battery. NaPF6 / EC:DMC electrolyte was injected, and constant current charge-discharge test was performed using the Xinwei Battery Test System at 30°C. The voltage range was set to 2.5-4V, and the cycle stability and rate performance were tested.

[0034] Comparative Example 1 The method for preparing the composite membrane as described in this embodiment includes the following steps: (1) Commercially available membranes were selected as comparative membranes without any inorganic coating or structural modification treatment.

[0035] (2) The commercial separator was assembled with sodium metal sheet and positive electrode (Na3V2(PO4)3@C@CNT) into a coin cell sodium-ion battery. NaPF6 / EC:DMC electrolyte was injected and constant current charge-discharge test was performed using the Xinwei Battery Test System at 30°C. The voltage range was set to 2.5-4V to test the cycle stability and rate performance.

[0036] Comparative Example 2 The method for preparing the composite membrane as described in this embodiment includes the following steps: (1) Weigh commercially available nanoparticle alumina (Al2O3) and polyvinylidene fluoride (PVDF) and mix them at a mass ratio of 14:1. Add the mixed powder to N-methylpyrrolidone (NMP) solvent, wherein the mass ratio of powder to solvent is 1:3. Stir at 700 r / min for 12 h at 60°C to obtain nanoparticle alumina slurry for membrane coating.

[0037] (2) The slurry is cast and coated on one side of the polypropylene membrane, the coating thickness is controlled to be about 10 μm, and then placed in a 40°C forced-air drying oven for 12 h; then the membrane is flipped over and coated and dried on the other side in the same way to obtain a double-sided coated nanoparticle alumina modified polyolefin membrane.

[0038] (3) The above-mentioned nanoparticle alumina modified separator, sodium metal anode and positive electrode are used to assemble a button sodium-ion battery. NaPF6 / EC:DMC electrolyte is injected into the battery and constant current charge and discharge test is performed using a battery test system at 30°C. The test voltage range is 2.5-4.0V to evaluate the cycle performance and rate performance of the battery.

[0039] Table 1 shows the long-cycle performance of batteries corresponding to Comparative Examples 1, 2 and Examples 3-5. In summary, this invention proposes a method for preparing a composite separator for sodium-ion batteries, comprising: preparing nanoscale ceramic fiber powder by electrospinning combined with high-temperature sintering; mixing the ceramic fiber powder with a binder in a solvent to form a coating slurry; casting the slurry onto at least one surface of a polyolefin porous base membrane, and drying it to form a porous coating containing ceramic fibers, thereby obtaining the composite separator. The ceramic fibers have nanoscale diameters and high aspect ratios, enabling them to form a continuous three-dimensional network structure in the coating. The composite separator prepared by this invention effectively improves sodium-ion transport efficiency while enhancing thermal stability, electrolyte wettability, and mechanical strength. When applied to sodium-ion batteries, the batteries exhibit excellent cycle stability and rate performance, with significantly improved capacity retention, demonstrating promising practical applications.

[0040] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a composite separator for sodium-ion batteries, characterized in that, Includes the following steps: Provides polyolefin porous base membranes; Ceramic fiber powder and binder are mixed in a solvent to form a coating slurry, wherein the ceramic fiber powder has a fibrous morphology; The coating slurry is applied to at least one surface of the polyolefin porous base membrane and dried to form a porous coating containing the ceramic fiber powder on the surface of the polyolefin porous base membrane, thereby obtaining the composite membrane.

2. The preparation method according to claim 1, characterized in that, The ceramic fiber powder is prepared by a method including the following steps: mixing a ceramic precursor sol with a polymer spinning aid and then electrospinning to obtain precursor fibers, and then subjecting the precursor fibers to sintering and crushing treatment.

3. The preparation method according to claim 2, characterized in that, The ceramic precursor sol is a sol containing at least one of aluminum, silicon, or zirconium; the polymeric spinning aid is at least one of polyvinyl alcohol, polyvinyl butyral, or polyvinylpyrrolidone.

4. The preparation method according to claim 2, characterized in that, The electrospinning voltage is 8-20 kV and the rotation speed is 100-1000 r / min; the sintering temperature is 800-1500℃.

5. The preparation method according to claim 1, characterized in that, In the coating slurry, the mass ratio of the ceramic fiber powder to the binder is 2:1 to 20:1, and the mass ratio of the ceramic fiber powder to the solvent is 1:1 to 1:

8.

6. The preparation method according to claim 1, characterized in that, The adhesive is a polymer adhesive, which includes oil-soluble adhesives and / or water-soluble adhesives; wherein the oil-soluble adhesive includes polyvinylidene fluoride, and the water-soluble adhesive includes at least one of carboxymethyl cellulose or polyethylene oxide; the solvent is a polar solvent that is compatible with the adhesive.

7. The preparation method according to claim 1, characterized in that, The method of applying the coating slurry to the surface of the base film is casting coating, and the drying temperature is 40-60°C.

8. The preparation method according to claim 1 or 7, characterized in that, The application step includes forming the porous coating on both opposite surfaces of the polyolefin porous base film, and the thickness of each porous coating after drying is independently 5-20 μm.

9. A composite diaphragm, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.

10. A sodium-ion battery, characterized in that, It includes the composite separator, positive electrode, sodium negative electrode, and electrolyte as described in claim 9.